Sulfur Source, Rate, and Methods of Application for Polyethylene-mulched Tomato - Anas D. Susila; Salvadore J. Locascio (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2005)
Tomato (Lycopersicon esculentum L.) was grown with polyethylene mulch and drip irrigation on a Millhopper fine sandy soil testing very high in P and low in organic matter during two seasons to evaluate the effect of S source, rate, and application methods on plant growth and yield of fruit. Sulfur rate of 34 and 68 kg S.ha-1 were applied with preplant (broadcast in the bed), drip (10 weekly drip application), and by split applications (50% preplant and 50% drip). In split applications, S sources evaluated were ammonium sulfate and ammonium thiosulfate. Plant height was increased with S application from 0 to 68 kg S.ha-1 in both studies. However, response on plant dry weight only occurred in spring 1999. Total marketable yield was 17.9 tons.ha-1 with 0 kg S.ha-1 and was increased linearly to 48.1 tons.ha-1 with application of 68 kg S.ha-1 in Spring 1999, but no response to S was obtained in the Spring 1998 study. Measured variables were not affected by S source and methods of application. Increasing S application from 0 to 68 kg S.ha-1 reduced leaf and plant tissue P concentration 14 and 12% at mid season, 26 and 25% at late season sampling times, respectively. S application of 68 kg S.ha-1 reduced soil pH approximately 0.3 unit at the end of the season in both studies. Key words: drip irrigation, sulfur, fertigation, Lycopersicon esculentum